Maximising sum rate for two interfering wireless links - Badruddin , Nasreen (2008)
In this paper, we consider the problem of maximising the sum rate of two interfering links in Gaussian noise. We assume no fading and that interference is treated as worst-case Gaussian noise, and that the optimal power allocation must be time-invariant. We show that either both links must operate at maximum power, or one link operates at maximum power and the other link is switched off. The switching point between one power scheme to another depends on the value of gamma which is the SNR of the link, as well as the channel gains at all links.